The Quality of Informed Consent in Caesarean Section at a Tertiary Hospital in Addis Ababa, Ethiopia - Ababulgu SN; Ethiopia SS; Bekele D (Dove Medical Press, 2022)
Sitra Nuredin Ababulgu,1 Samrawit Solomon Ethiopia,2 Delayehu Bekele3 1St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2School of Public Health. St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia; 3Department of Obstetrics and Gynecology, St. Paul's Hospital Millennium Medical College, Addis Ababa, EthiopiaCorrespondence: Sitra Nuredin Ababulgu, Tel +251920157625, Email ms_sitra.nuredin@sphmmc.edu.etPurpose: The absence of high-quality and timely informed consent creates a barrier between the health-care provider and the patient that reinforces a negative view of the healthcare system, deters utilization of health-care services and increases malpractice lawsuits. This research aimed to assess the quality of informed consent in cesarean section (CS) at a large tertiary care center in Ethiopia.Patients and Methods: An institutional cross-sectional study was conducted on 288 women who underwent planned or emergency CS. A structured questionnaire for respondents with standard indicators was developed as per the recommendations of the Royal College of Surgeons for the evaluation of the completeness of the informed consent document on the medical records.Results: The median (IQR) age of the participants was 28 (25.0- 32.0) years and 203 (70.5%) has undergone emergency CS. More than half of the respondents 172 (59.7%) were unaware of who would perform the surgery and only 50 (17.4%) of respondents stated they were informed of complications of the CS. A total of 157 (56.3%) of responses fulfilled the criteria for adequate subjective informed consent with an affirmative response while only 109 (37.9%) of responses fulfilled the criteria for adequate objective informed consent. Only educational status of the patient was associated with subjective adequacy of informed consent with those who have some formal education having 2.05 times odds of having adequate subjective consent as compared to those with no formal education.Conclusion: In this study, we have found that women undergoing CS receive inadequate informed consent. This inadequate informed consent occurs across planned and emergency CS. The results highlight the need for better consent process to increase patient awareness and promote patient-centered-care.Keywords: quality, informed consent and cesarean section